Function of plants for ibuprofen removal in constructed wetland - Chen, LiHui (2014)
Pharmaceutical products have been progressively used over the last decade and particularly Ibuprofen which is commonly found as a pharmaceutical feed ingredient. As a result, Ibuprofen has been continuously discharged into aquatic environments via excreta of individuals, improper drugs disposal methods and limitations in wastewater treatment plant, posing a threat to both environment and human health. To mitigate this threat, constructed wetland is viewed as a cost effective alternative solution that exploits natural treatment technique in Ibuprofen extraction from wastewater. The research will aim to investigate the uptake and translocation of Ibuprofen within Typha angustifolia in mesocosm-scale horizontal subsurface flow constructed wetland (HSSF-CW). Experiments were conducted with synthesized wastewater spiked with 100 µg/L of Ibuprofen that was constantly fed into a planted and unplanted wetland bed. Firstly, results showed clearly both wetlands have demonstrated positive removal of nutrients such as COD, NH4+ and TP. Comparatively, a planted bed has attained higher removal efficiencies of 93% in COD, 66% in NH4+ and 74% in TP as compared to 89%, 30% and 22%, respectively, in the unplanted bed. Secondly, sea sand disruption method and LC-MS/MS was adopted in the analysis of the mass fraction of Ibuprofen and its metabolites, namely carboxy-Ibuprofen, 1-hydroxy-Ibuprofen and 2-hydroxy-Ibuprofen, uptake within the plants. An average mass fraction of 235 ng/g, 293 ng/g, 149 ng/g and 237 ng/g were detected respectively. Thirdly, diffusion was found to be the mechanism responsible for the translocation of such target compounds within plant tissues and thereafter, log octanol-water partitioning coefficient is used to characterize its efficiencies. The study successfully revealed the uptake and translocation capabilities of Ibuprofen in Typha angustifolia and the overall efficiency of HSSF-CWs in the removal of nutrients and pharmaceuticals from wastewater. These findings would be benchmarked for future studies on the removal of emerging pharmaceuticals products in environmental water bodies. The directions of future research studies can include analyzing the concentration of target compounds in the root zone of plants and investigating the removal efficiency of pharmaceuticals in large-scale treatment wetland under outdoor environmental conditions.